(untitled) (Journal of the College of Languages (JCL), 2020)
Idiomatic expressions in Russian journalism make one important borrowed means for making a dialogue with the receiver’s intellect in so far as it has the distinct feature of having clarity and exactness of meaning. The meaning is seen as a shortcut for covering a series of concepts and details so as to arrive at the intended meaning. This is done by stimulating the reader by the use of certain clear idioms. The use of such idioms in a journalistic text is not for a linguistic purpose only, but it is a cultural and social phenomenon reflecting the type of current changes in the society and it aims at discoursing with the reader’s mind. This paper is a practical attempt to the continuous use of idiomatic expressions in the selected journalistic text samples from a number of Russian newspapers. Аннотация. Именно поэтому цель данной работы включается в том, чтобы проявить, каковы важнейшие чередования и изменения, которым подвергаются фразеологические единицы, употребляемые в языке современной Российской прессы. В статье рассматривается важность использования Фразеологических единиц в прессе в качестве лингвистического средства, которое передает текст жизнеспособность и блеск вниманию читателя. Использование ФЕ в прессе является не только лингвистическим, но и культурным и социальным явлением, отражающим проходящие изменения в обществе. Использование фразеологизма в газете усиливает экспрессию предложения, мастерит его более, ярким по смыслу высказыванием. Авторы газетных статей могут употреблять прямое цитирование — отражение фразеологических единиц разнообразных типов и образов в той картине, в которой они имеются в газетном языке.